TAREQAH NAQSYABANDIYAH AND ITS IMPACT ON CHARACTER REFINEMENT IN SOUTH SULAEWSI - Hadarah Rajab (Universitas Islam Negeri Alauddin Makassar, 2012)
To Muslim societies, especially of those inclining to sufism, Tareqah Naqsyabandiyah is particularly outstanding. This is mainly due to the wide spread and broad influence of the Tareqah teachings in different parts of the world. In Indonesia, the influence of Tareqah Naqsyabandiyah teachings is scattered in almost all areas of the country, including in South Sulawesi. For the people of South Sulawesi, the position of Tareqah Naqsyabandiyah is highly essential as it is closely related to the greatest scholar of the region, Shaykh Yusuf al-Makassari, who is believed to be the first to introduce Tareqah Naqsyabandiyah in Indonesia. This paper examines methods developed to obtain fundamental values in Tareqah Naqsyabandiyah. More specifically, it will also examine the Tareqah teachings practiced by the people of South Sulawesi. The exploration flows from the historical aspect to elaborate the role of Murshid and the practical benefits affecting the social life in South Sulawesi, especially with regards to worship and muamalah.